A Wel(l)come development: research funders and open access - Pinfield, Stephen (2006)
This paper discusses the implications of the Wellcome Trust agreement with Blackwell, OUP and Springer in which authors of accepted papers are able to pay an open-access publication charge to make their article freely available online. In bringing together flexible licence terms and clear funding streams, the agreement has the potential to be used as a way of migrating towards possible new business models for journal publishing. It also has the potential, if implemented more widely, to deliver greater open access in such a way as to work in the interests of a broad range of stakeholders.